On the links between positive religious coping, satisfaction with life and depressive symptoms among a multinational sample of Muslims - AYTEN, ALİ (JOHN WILEY & SONS LTD, 2019)
This study tested the levels and consequences of positive religious coping among a multinational sample of Muslims. The sample consisted of 706 university students recruited in three Muslim countries: Israel/Palestine, Turkey and Malaysia. Participants' average age was 22.61, and 65% of them were females. This investigation applied a cross-sectional comparative methodology. Measures used: demographics, positive religious coping, satisfaction with life and depressive symptoms. The findings indicated that (a) participants reported high levels of positive religious coping usage, and Malaysians scored significantly higher in this regard than both Palestinians and Turks; (b) positive religious coping correlated positively with satisfaction with life but was not linked to depressive symptoms and (c) the magnitude of correlation between positive and satisfaction with life was significantly higher among Malaysians than among both Palestinians and Turks. The findings suggest that to understand the implications of positive religious coping for the health and well-being of Muslims, a detailed and nuanced analysis is needed.
Keywords: Positive religious coping; Muslims; Satisfaction with life; Depressive symptoms; NATIONAL SAMPLE; DISORDER; STRESS